Ogólna charakterystyka Policji jako formacji uzbrojonej i umundurowanej oraz jej wielowymiarowość - Rudnicka, Magdalena (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The article is devoted to general characteristics of the Police as a formation of armed and uniformed. The design of this study shows the many aspects of the Police in the context of its overall analysis of the structure and explanation of the tasks performed by it. The aim of the article is to present the Police as an formation with extensive powers which consists of its multidimensional nature. The article contains the outline of the system of selection of candidates to serve in the police. It shows also the issue of the ethical aspects of the profession of police officer.